Effect of Electronic Money Transactions on Customer Satisfaction According to Sharia Economy (Case Study at STAI La Tansa Mashiro) - Budiman, Budiman; Adawiyah, Endah Robiatul; Syukri, Mahmud; Ibadurohmah, Ibadurohmah; Wahrudin, Udin (AL-FALAH : Journal of Islamic Economics, 2023)
Purpose: This paper examines the Effect of Electronic Money Transactions on Consumer Satisfaction According to Sharia Economics on STAI La Tansa Mashiro Students.Design/Method/Approach: This research uses descriptive quantitative with 110 samples. Sampling was carried out using purposive sampling method with 2 categories, namely activity and use of the OVO or Go pay e-wallet application to make transactions, to objectively measure socio-economic phenomena in electronic money transactions on consumer satisfaction.Findings: The results show a positive and significant effect, Electronic Money Transactions on Consumer Satisfaction. Where the t test results are 3.724 and t table 1.659 significant level <0.05, namely 0.001 <0.05, then t count> from t table 3.724> 1.659. Explaining that Ho is rejected and Ha is accepted. The t test results are reinforced with (RÂ²) 0.114.Organally/Value: There is a positive and significant effect of Electronic Money Transactions on Consumer Satisfaction. With t test results of 3.724 and t table 1.659 with a significant 0.001 <0.05, then t count> t table 3.724> 1.659. Then Ho is rejected and Ha is accepted. The t test results were strengthened (RÂ²) 0.114. Sharia Economic Perspective DSN MUI Fatwa No. 116 of 2017 states that legal electronic money can be used as a means of payment by following the provisions of this fatwa.